Resilience Building and Climate Change Adaptation for Coastal Communities (Model building for small municipalities in the Philippines) - International Institute of Rural Reconstruction (2019)
CCAFS supported the International Institute of Rural Reconstruction (IIRR) and the local government unit of Guinayangan to test and develop an initial set of coastal interventions, such as: mangrove nursery establishment; and reforestation and restoration of mangroves.